A Hierarchically Porous Carbon Fabric for Highly Sensitive Electrochemical Sensors. Issue 1 (23rd August 2017) - Jiao, Yuan; Cho, Seong Won; Lee, Suyoun; Kim, Sang Hoon; Jeon, Seung‐Yeol; Hur, Kahyun; Yoon, Sun Mi; Moon, Myoung‐Woon; Wang, Aiying
Abstract : The hierarchically porous carbon fabrics with controlled conductivity and hydrophilicity have been fabricated by dual templating method of soft templates nested on hard templates. A non‐woven fabric coated with a solution of F127/resol has been carbonized for the synthesis of both macro‐porous structures of 10–15 µm in diameter having meso‐porous carbon structures of 4–6 nm, respectively. After carbonization treatment, not only conductivity is significantly improved, the hierarchically porous carbon also shows superhydrophilicity or water‐absorbing nature due to mild hydrophilic material and its dual scale roughness. The porous carbon becomes conductive with resistivity widely tuned from 5.4 × 10 3  Ωm to 3.1 × 10 −3  Ωm by controlling the carbonization temperature. As the increased wettability for organic liquids could lead organic molecules deep into carbonized fabrics, the sensitivity of hierarchically porous carbon fabrics benefits the detection for methanol(CH3 OH) or hydrogen peroxide (H2 O2 ). This new design concept of hierarchically porous structures having the multi‐functionality of high wettability and conductivity can be highly effective for electroanalytical sensors. Abstract : Hierarchical porous carbon fabrics with controlled conductivity and hydrophilicity have been fabricated by dual templating. The hydrophilicity and conductivity work synergistically, making the porous carbon material a good candidate for electrochemical sensor.